2019
DOI: 10.1007/s10546-019-00460-5
|View full text |Cite
|
Sign up to set email alerts
|

Observing the Whole-Canopy Short-Term Dynamic Response to Natural Step Changes in Incident Light: Characteristics of Tropical and Temperate Forests

Abstract: We examine the physical and biological responses of forest canopies to step changes in light caused by passing low cumulus clouds that intermittently block the direct solar beam. Using data obtained at a tropical rainforest and at a midlatitude deciduous forest, we estimate the course of sensible heat flux, net ecosystem exchange, evapotranspiration, and water-use efficiency in response to the rapid changes in the incident radiative flux. To describe these fluxes during the interval over which the effects of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 119 publications
0
9
0
Order By: Relevance
“…The treatment of such transient conditions is a challenge for current methods used to determine surface turbulent fluxes since they assume stationarity. Conditional sampling strategies have been developed over forests with dense canopies byKivalov and Fitzjarrald (2019): they found that ET takes between 5 to 10 min to respond to a change of solar irradiation, in contrast to the air and leaf temperature that change more rapidly.…”
mentioning
confidence: 99%
“…The treatment of such transient conditions is a challenge for current methods used to determine surface turbulent fluxes since they assume stationarity. Conditional sampling strategies have been developed over forests with dense canopies byKivalov and Fitzjarrald (2019): they found that ET takes between 5 to 10 min to respond to a change of solar irradiation, in contrast to the air and leaf temperature that change more rapidly.…”
mentioning
confidence: 99%
“…This assumption is supported by the Global Space-based Stratospheric Aerosol Climatology time series (1979-2016Thomason et al, 2018). The time series of cloud fraction is derived from the 6-hourly cloud distributions simulated by the Japanese Reanalysis (JRA; Kobayashi et al, 2015) and is scaled to match the monthlyaveraged cloud cover in the CRU TS v4.03 dataset (Harris et al, 2014). The surface radiative fluxes calculation considered aerosol-radiation interactions from both tropospheric and stratospheric aerosols, and for aerosol-cloud interactions from tropospheric aerosols, except mineral dust.…”
Section: Forcing Data and Experimental Designmentioning
confidence: 96%
“…The climate forcing used in this study is the 6 h CRUJRA v1.1 dataset (Harris et al, 2014;Harris, 2019;Kobayashi et al, 2015). The CRUJRA v1.1 dataset was generated by adjusting the Japanese Reanalysis data (JRA) produced by the Japanese Meteorological Agency (JMA) with the observationally based monthly Climatic Research Unit (CRU) TS 3.26 data.…”
Section: Forcing Data and Experimental Designmentioning
confidence: 99%
“…with Fdf. In this study, we investigated the impact of Fdf alone for which there are several explanations (e.g., (Roderick et al , 2001;Kivalov and Fitzjarrald, 2019)). Among these, the most widely accepted explanation is that compared with direct 9 https://doi.org/10.5194/gmd-2020-267 Preprint.…”
Section: Seasonal and Diurnal Variations Of ∆Gppmentioning
confidence: 99%